Pidana Penjara dalam Perspektif Hukum Pidana Islam: Analisis Kritis terhadap Efektivitas dan Tujuan Pemidanaan: Imprisonment from the Perspective of Islamic Criminal Law: A Critical Analysis of the Effectiveness and Purpose of Punishment - Isparizan Saputra; Hafidz Syahdan; Dwi Septianingsih; Asrizal Saiin (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2026)
This study aims to analyze imprisonment from the perspective of Islamic criminal law by highlighting the effectiveness and objectives of punishment. Imprisonment as a form of modern punishment is not explicitly found in the text, but the practice of restricting freedom has been known in the history of Islamic law. Through a legal-normative approach and critical analysis, this study evaluates whether imprisonment is in line with maqashid al-syari'ah, particularly in protecting religion, life, reason, lineage, and property. The results of the study show that although imprisonment can fulfill the objectives of prevention (zajr) and education (ta'dib), its effectiveness is questionable when faced with issues of overcapacity, dehumanization, and low deterrent effect in society. This study recommends reformulating the concept of punishment to emphasize restorative and rehabilitative aspects in accordance with the principle of substantivejustice in Islamic criminal law. Penelitian ini bertujuan untuk menganalisis pidana penjara dalam perspektif hukum pidana Islam dengan menyoroti efektivitas dan tujuan pemidanaan. Pidana penjara sebagai bentuk hukuman modern tidak ditemukan secara eksplisit dalam nash, namun praktik pembatasan kebebasan telah dikenal dalam sejarah hukum Islam. Melalui pendekatan yuridis-normatif dan analisis kritis, penelitian ini mengevaluasi apakah pidana penjara selaras dengan maqashid al-syari’ah, khususnya dalam menjaga agama, jiwa, akal, keturunan, dan harta. Hasil kajian menunjukkan bahwa meskipun pidana penjara dapat memenuhi tujuan pencegahan (zajr) dan pendidikan (ta’dib), efektivitasnya dipertanyakan ketika berhadapan dengan persoalan overkapasitas, dehumanisasi, serta rendahnya efek jera di masyarakat. Penelitian ini merekomendasikan reformulasi konsep pemidanaan agar lebih menekankan aspek restoratif dan rehabilitatif sesuai prinsip keadilan substantif dalam hukum pidana Islam.